Here's the question you clicked on:
blondebaby42911
If you were to use the elimination method to solve the following system, choose the new system of equations that would result after the variable y is eliminated in the first and second equations, then the second and third equations.3x – y + 3z = 1 4x + y – 6z = 3 4x – 2y + 3z = –3
As a start: 7x - 3z =4 would be the result of eliminating y combining the first two equations.
12x -9z=3 eliminating y using the last two equations.
Do you have to ultimately solve this system?